Menanam sebelum kiamat : Islam, ekologi, dan gerakan lingkungan hidup - Mangunjaya, Fachruddin M., 1964-; Heriyanto. Husain; Gholami, Reza.; Conservation International. Indonesia Program (Jakarta : Conservation International Indonesia : Islamic College for Advanced Studies, 2007)
Ecology and environmental conservation issues in Indonesia from Islamic point of view; collection of articles.
Includes bibliographical references and index.
In Indonesian, with summaries in English.
Keywords: Environmentalism -- Islamic countries; Environmental ethics -- Islamic countries; Islamic countries -- Environmental conditions